2009
DOI: 10.2478/v10010-009-0028-0
|View full text |Cite
|
Sign up to set email alerts
|

On Hearing Colours — Cross-Modal Associations in Vowel Perception in a Non-Synaesthetic Population

Abstract: The present study is a continuation of previous investigations into the nature of sound−colour associations in a non-synaesthetic population conducted on English and Polish vowel sound systems and it aims at providing further evidence for the non-arbitrary nature of cross-modal mappings. The experiment 1 was run on a specially designed computer program and involved 90 participants who were asked to match randomised auditory stimuli (12 English vowel sounds recorded in 2 conditions: in isolation and in a CVC co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 10 publications
3
28
0
Order By: Relevance
“…Almost the same pattern of correspondence was found in our previous study [12], so that we conclude that the pattern of correspondence between colors and vowels in Japanese non-synesthetes is stable. The results in this study also showed resemblance to the Polish results of Wrembel [13], suggesting that certain aspects of the correspondence between colors and vowels are universal. In experiment 1 some additional effects of gender and the pitch of voices were also shown.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Almost the same pattern of correspondence was found in our previous study [12], so that we conclude that the pattern of correspondence between colors and vowels in Japanese non-synesthetes is stable. The results in this study also showed resemblance to the Polish results of Wrembel [13], suggesting that certain aspects of the correspondence between colors and vowels are universal. In experiment 1 some additional effects of gender and the pitch of voices were also shown.…”
Section: Discussionsupporting
confidence: 78%
“…Yet the correspondence between red and /a/ is not limited to Japanese [16]. These patterns of correspondence including the case of red and /a/ were found across languages and types of synesthesia [9,13,16]. So beyond language specific label effects, there must reside some common factors.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study are also very much in line with a series of experiments on multimodal sound-colour correspondence in L1 and L2 in a nonsynaesthetic population (Wrembel 2007(Wrembel , 2009Wrembel & Rataj 2008). The vowelcolour interactions generated in these studies demonstrated non-arbitrary patterns of distribution, in which specific phonemic features triggered particular colour attributes, namely front vowels were associated with bright colours; back vowels with darker hues; open vowels generally with red; and central vowels with achromatic grey.…”
Section: Discussionsupporting
confidence: 78%
“…In the present section the findings are first interpreted and then compared against other studies on sound symbolism and synaesthesia as well as a series of experiments on sound-colour coding conducted by the present author (Wrembel 2007, Wrembel & Rataj 2008, Wrembel 2009.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation